Non-Operative Management Accelerates Recovery: Reduced Length of Hospital Stay in Partial Small Bowel Obstruction with Virgin Abdomens - Aryani, Prathita Amanda; Abdul Mughni (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Small bowel obstruction (SBO) represents a formidable challenge in surgical practice. Partial SBO (PSBO) in individuals without a history of abdominal surgery, termed "virgin abdomens," introduces distinct diagnostic and therapeutic considerations. While non-operative management (NOM) has become a cornerstone for adhesive SBO, comprehensive data elucidating its impact on PSBO in virgin abdomens, especially concerning the length of hospital stay (LOS), are not extensively available. This study was designed to meticulously compare the LOS between NOM and operative interventions in patients diagnosed with PSBO affecting virgin abdomens, specifically within a tertiary care setting in Indonesia. Methods: A retrospective analytic observational methodology, utilizing a cross-sectional design, was implemented at Dr. Kariadi General Hospital, Semarang, covering patients admitted from January through December 2024. The study included patients over 18 years of age with a confirmed diagnosis of PSBO in a virgin abdomen. Exclusion criteria encompassed total SBO, obstructions located in the colon, or any record of prior abdominal surgical procedures. The principal outcome measure, LOS, was rigorously compared between the cohort managed non-operatively and the cohort that underwent surgical procedures. Statistical analysis was performed using appropriate tests, with a p-value below 0.05 established as the threshold for statistical significance. Results: The study cohort comprised 167 eligible patients. For the 112 patients (67.1%) subjected to surgical intervention, the mean LOS was recorded at 13.2±8.72 days. Conversely, the 55 patients (32.9%) managed conservatively demonstrated a markedly shorter mean LOS of 7.74±6.12 days. This observed difference in LOS was statistically highly significant (p < 0.001). The mean age of the participants was 50.60±14.94 years, with females constituting 52.1% of the group. Conclusion: In clinically stable patients presenting with partial small bowel obstruction in virgin abdomens, non-operative management was associated with a significantly diminished length of hospital stay when compared to surgical intervention. This conservative strategy proves to be an effective and advantageous approach in appropriately selected patient populations, offering the potential to lessen hospital burden and enhance recovery timelines.